Heteragrion gorbi sp. nov. (Odonata: Heteragrionidae) from southeastern Brazil - Cezário, Rodrigo Roucourt; Guillermo-Ferreira, Rhainer (Zootaxa, 2021)
Heteragrion gorbi sp. nov. (Zygoptera: Heteragrionidae) is described and diagnosed based on six ♂♂ and one ♀. The specimens were collected in a stream in a Neotropical savannah fragment in São Carlos, São Paulo, Brazil. We present pictures of the holotype and the female. This is a species with blue coloration pattern, rare among its congeners.